Upaya Kepala Sekolah dalam Meningkatkan Kinerja Guru Melalui Supervisi Akademik di SD Negeri 1 Kangkung OKU Timur - Zaidan; Kiki Melita Andriani; Indah Maysela Azzahra; Rz. Ricky Satria Wiranata (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2021)
One of the efforts that the principal can make in improving the quality of teacher performance is through academic supervision. The main mission of academic supervision is to provide services to teachers to develop the quality of lessons and facilitate teachers to teach effectively. This study uses the interview method. The results of this study indicate that in general the supervision process carried out by the principal has been carried out well, in particular the implementation of supervision is oriented towards maintaining the existing teacher performance process, so that it has not made efforts to develop gradually due to limited costs. Researchers found four stages carried out by the principal in carrying out academic supervision, namely planning, evaluation and follow-up.